Age-Related Memory Impairment and Sex-Specific Alterations in Phosphorylation of the Rpt6 Proteasome Subunit and Polyubiquitination in the Basolateral Amygdala and Medial Prefrontal Cortex - Dulka, Brooke N.; Trask, Sydney; Helmstetter, Fred J. (Frontiers in Aging Neuroscience, 2021)
Aging is marked by an accumulation of damaged and modified brain proteins, and the ubiquitin-proteasome system (UPS) is important for cellular protein degradation. Recent work has established a critical role for the UPS in memory and synaptic plasticity, but the role of the UPS in age-related cognitive decline remains poorly understood. We trained young, middle-aged, and aged male and female rats using trace fear conditioning to investigate the effects of age and sex on memory. We then measured markers of UPS-related protein degradation (phosphorylation of the Rpt6 proteasome regulatory subunit and K48-linked polyubiquitination) using western blots. We found that aged males, but not aged females, showed behavioral deficits at memory retrieval. Aged males also displayed reduced phosphorylation of the Rpt6 proteasome subunit and accumulation of K48 in the basolateral amygdala, while aged females displayed a similar pattern in the medial prefrontal cortex. These findings suggest that markers of UPS function are differentially affected by age and sex in a brain region-dependent manner. Together these results provide an important step toward understanding the UPS and circuit-level differences in aging males and females.